Implementation Of Staple Food Program For Beneficiary Families In Sawah Kulon Village Pasawahan District Purwakarta Regency - Gina Anaimah; Ali Anwar Yusuf; Willya Achmad (Jurnal EduHealth, 2023)
This research is entitled "Implementation of the Staple Food Program for Beneficiary Families (KPM) in Sawah Kulon Village, Pasawahan District, Purwakarta Regency". which have been determined and implementation itself refers to various program implementation actions that have been prepared to achieve the planned program objectives. The Indonesian government is conducting business through social assistance programs that aim to reduce the level of poverty that occurs in Indonesia, one of which is with the assistance of the Basic Food Program, the basic food program is food social assistance that is distributed in non-cash form from the government to KPM every month via electronic money which is used only for buy groceries. The research method used is a qualitative approach method with informant selection techniques using purposive sampling. Data collection techniques in this study used techniques, namely: (1) Interview (2) Observation (3) Documentation Study. The number of informants in this study was divided into three parts, namely the main informants who were beneficiaries of eight families, the key informants, namely the Pasawahan District Social Welfare Workers and additional informants, namely the Village Secretary. The results of the study showed that the implementation of the basic food program went well, no serious obstacles were found and had a positive impact on beneficiary families.